CHARACTERIZATION OF THE SUPPLY CHAIN IN THE HORTICULTURAL PRODUCTION PROCESS UNDER THE SCOR MODEL IN THE PROVINCE OF TUNDAMA, BOYACÁ - M, Serrano-Amado, Ana; C, Sanabria-Neira, Nancy; M, Chávez-Otálora, Alba (Journal of Posthumanism, 2025)
This study characterizes the supply chain of the horticultural sector in the province of Tundama, Boyacá (Colombia), using the SCOR (Supply Chain Operations Reference) model as a guiding framework. Through a mixed-method approach—combining bibliometric analysis, surveys, interviews, and statistical processing—the research identifies critical gaps and improvement opportunities in the areas of production, sourcing, distribution, marketing, and sustainability. The findings reveal a predominantly traditional agricultural structure with limited adoption of advanced technologies, infrastructure deficiencies, high logistical costs, and weaknesses in marketing channels and customer loyalty. Despite these challenges, there is a high willingness among producers to adopt technological innovations and improve sustainability practices. The application of the SCOR model facilitated a comprehensive diagnosis of the chain's strengths and weaknesses, laying the foundation for strategic improvements and more resilient, competitive horticultural supply chains in the region.